Orchestrated regulation of immune inflammation with cell therapy in pediatric acute liver injury - Duan, Mingyue; Liu, Xiaoguai; Yang, Ying; Zhang, Yanmin; Wu, Rongqian; Lv, Yi; Lei, Hong (Frontiers in Immunology, 2023)
Acute liver injury (ALI) in children, most likely leading to acute liver failure (ALF) with the need of liver transplantation, is a devastating life-threatening condition. As the orchestrated regulation of immune hemostasis in liver are essential for timely resolving excess inflammation and promoting liver repair, we focused on the immune inflammation and regulation with the functional involvement of both innate and adaptive immune cells in acute liver injury progression. In the context of the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic, incorporating insights from the immunological perspective was also provided for the hepatic involvement with SARS-CoV-2 infection, as well as the acute severe hepatitis of unknown origin in children since firstly reported on March 2022. Furthermore, molecular crosstalk between immune cells concerning the roles of damage associated molecular patterns (DAMPs) in triggering immune responses through different signaling pathways play essential roles in the process of liver injury. DAMPs such as high mobility group box 1 (HMGB1), cold-inducible RNA-binding protein (CIRP), as well as macrophage mitochondrial DNA-cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) signaling pathway in liver injury, were further focused on. In addition, novel therapeutic approaches targeting molecular and cellular crosstalk and cell-based therapy were highlighted with the future outlook.